Fungsi Pelacakan Alumni Guna Meningkatkan Mutu Pendidikan - Endang Wahyuni; Ade M. Yuardani; Verdico Arief (Jurusan Akuntansi Politeknik Negeri Pontianak, 2018)
The function of alumni tracking or commonly called tracer study to improve the quality of education is a research that intends to know how far the role and influence and how the implementation of taracer study activities in order to improve the quality of education. This research takes case study in Study Program D-IV Public Administration State Polytechnic of Pontianak. The research of alumni tracking function to improve the quality of education is done qualitatively. This is done so that researchers can get actual and indepth data about the function of the alumni tracking activities. Whether the alumni tracking activity has a positive benefit or just the opposite. From the results of research that has been done got the results that the actual implementation of alumni tracking activities have quite a variety of functions. As well as promotional media or a means to introduce institutions to the wider community, establishing good relationships between alumni and institutions, a reference for institutions in preparing accreditation forms as well as a reference evaluation of the learning curriculum for the institution concerned.